The Influence of Financial Inclusion on Stock Market Participation in Nepal: Exploring the Mediating Effect of Financial Knowledge - Shrestha, Purna Man; Rana, Mahesh (Journal of Mathematics Instruction, Social Research and Opinion, 2024)
This paper focuses on financial inclusion (FI), a fast-embracing topic with potential drivers of economic growth and the improvement of individual financial well-being. This study contributes to the existing literature by analysing how financial inclusion influences stock market participation (SMP) in Nepal, explicitly emphasising the intermediary role of economic knowledge. The study employed a causal-comparative research design, and the data were collected from 403 individual investors actively participating in the Nepal Stock Exchange (NEPSE) trading. The statistical tools used to meet the objectives of this research are descriptive statistics, factor analysis, and structure equation modelling. The study results show that FI and knowledge influence individual investor participation in the stock market. The result also indicates that FI is positively related to stock market activity, while it is essential to enhance citizens' FK significantly. Further, mediation analysis shows that FK partially mediates the relationship between FI and SMP. This suggests its pivotal role in narrowing the gap between access to financial services and actual investment behaviour. These findings underscore the critical role of FI in creating an inclusive and participatory financial ecosystem within Nepal. Longitudinal data in future research can capture the evolving dynamics of FI and its long-term impact on SMP.